Empowering growth: Training Burundi’s next generation of women and youth common bean seed producers - Hakizimana, Benadette; Ntawuyankira, Neilla; Ndabashinze, Blaise; Nchanji, Eileen (2024)
Common beans are classified among the top subsistence crops in Burundi. They are a staple food present in almost every meal and provide 20% of calories and 50% of proteins. Beans offer exceptional potential to contribute to the fight against micronutrient deficiencies. They are the most widely grown and consumed legume in Burundi, serving as the main staple food and primary source of proteins, carbohydrates, and micronutrients, particularly iron (Fe), zinc (Zn), and vitamins. Despite these advantages, smallholder farmers, particularly women and disadvantaged groups, are especially vulnerable to climate-related challenges and other factors, which undermine their ability to meet their own food, nutrition, and income needs, let alone contribute to local and national food security and income. More frequent droughts and irregular rainfall due to climate change threaten agricultural production in general and bean production in particular. Furthermore, due to an inadequate seed supply and poorly adapted distribution systems that fail to meet user and market demand, smallholder farmers often resort to using “old” or recycled seeds, making them more vulnerable to pests and diseases. It is within this context that the SeedEqual initiative co-designed multiple trainings to build the capacity of farmers to produce and sell good quality seed for increased productivity, income and empowerment. Institut des Sciences Agronomiques du Burundi (ISABU), through the Pan African Bean Research Alliance- a program under the Alliance of Bioversity International and CIAT, aims to support the production and delivery of improved seeds of priority crop varieties that are climate-resilient, market-preferred, and nutritious to farmers, while ensuring equitable access for women and other disadvantaged groups. Thus, a gendered seed production and marketing training was organized with particular attention given to women and youth (young women) seed producers.